2010
DOI: 10.1111/j.1399-3046.2010.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Living related liver transplant following bone marrow transplantation from same donor: Long‐term survival without immunosuppression

Abstract: We report long-term (seven yr) immunological tolerance in a 16-yr-old boy, to a liver allograft donated by his father following a bone marrow transplant at age 2.5 yr from the same donor. The bone marrow transplant was complicated by severe GVHD leading to liver failure and the ensuing need for a liver transplant, performed under planned avoidance of immunosuppression. At one wk post-transplant, although a liver biopsy was histologically compatible with acute rejection, favorable clinical and biochemical evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We observed such a child showing a persistent state of immunological tolerance 7 years after transplant without IS at any stage. Appropriate studies showed complete donor chimerism in the recipient's peripheral blood Can immunological tolerance be induced in clinical practice?…”
Section: Developments Leading To the Current Success In Pediatric LIVmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed such a child showing a persistent state of immunological tolerance 7 years after transplant without IS at any stage. Appropriate studies showed complete donor chimerism in the recipient's peripheral blood Can immunological tolerance be induced in clinical practice?…”
Section: Developments Leading To the Current Success In Pediatric LIVmentioning
confidence: 99%
“…Appropriate studies showed complete donor chimerism in the recipient's peripheral blood. (55) Can immunological tolerance be induced in clinical practice? Microchimerism, with less than 1% of donor cells detected, might be the clue.…”
Section: Immunological Privilege Of the Livermentioning
confidence: 99%
“…No immunosuppression was given to 1 patient who received, before LT, bone marrow transplantation from the same LD. 10 Acute rejection (AR) was diagnosed in case of elevated liver enzymes and/or cholestasis with a biopsy-proven graft rejection (BANFF score) 11 and treatment by intravenous methylprednisolone.…”
Section: Posttransplant Management Of Pediatric Recipientsmentioning
confidence: 99%
“…In regard to type of transplant, ie, LDLT versus DDLT or pediatric versus adult, the Kyoto group demonstrated a high IS withdrawal success rate (42.6%) fairly early after pediatric LDLT 55, 56. Other case series have reported IS withdrawal in recipients of simultaneous or staggered donor hematopoietic cell transplantation and LDLT 51, 68‐71. The success of these approaches may be in part due to greater HLA similarities between the related donor/recipient pairs or the avoidance of significant ischemia/reperfusion injury by the nature of the procedure.…”
Section: Immunosuppression Withdrawal: Learning From the Pastmentioning
confidence: 99%